Some corrections to the notation of verse structure in two recent editions of Middle English alliterative poems - IAN CORNELIUS (Filologia Germanica)
In Germanic alliterative verse the fundamental unit of meter and rhythm is the half-line. Editions of older Germanic alliterative poems now usually record this feature in their typographic design: the poetry is lineated and coordinate half-lines are separated with whitespace. For Middle English alliterative poems, the usual presentation has been in undivided long lines, but several recent editions separate half-lines with whitespace or punctuation marks. The present essay examines the half-line divisions in John Burrow and Thorlac Turville-Petre’s Piers Plowman B (2014/2018) and Ad Putter and Myra Stokes’s Cleanness, Patience, and Sir Gawain and the Green Knight (2014). Burrow and Turville-Petre aim to reconstruct the metrical markings of the archetypal scribe, whereas Putter and Stokes divide on the basis of their understanding of meter. I offer corrections to both editions, beginning with several lines in which Burrow and Turville-Petre misreport evidence for scribal notation of verse structure. In the edition by Putter and Stokes I find no misdivisions in Cleanness or Patience, but several errors and difficult cases in Gawain. I propose new emendations to Gawain 1281 and 1884.